Local Protocols for Contracting and Expanding Robot Formation Problems - Castenow, Jannik

Online Algorithms for Allocating Heterogeneous Resources - Knollmann, Till

Efficient Modeling and Tailoring of Nonlinear Wavefronts in Dielectric Metasurfaces - Hähnel, David; Förstner, Jens; Myroshnychenko, Viktor (ACS Photonics)
Dielectric metasurfaces provide a unique platform for efficient harmonic generation and optical wavefront manipulation at the nanoscale. Tailoring phase and amplitude of a nonlinearly generated wave with a high emission efficiency using resonance-based metasurfaces is a challenging task that often requires state-of-the-art numerical methods. Here, we propose a simple yet effective approach combining a sampling method with a Monte Carlo approach to design the third-harmonic wavefront generated by all-dielectric metasurfaces composed of elliptical silicon nanodisks. Using this approach, we theoretically demonstrate the full nonlinear 2π phase control with a uniform and highest possible amplitude in the considered parameter space, allowing us to design metasurfaces operating as third harmonic beam deflectors capable of steering light into a desired direction with high emission efficiency. The TH beam deflection with a record calculated average conversion efficiency of 1.2 × 10–1 W–2 is achieved. We anticipate that the proposed approach will be widely applied as alternative to commonly used optimization algorithms with higher complexity and implementation effort for the design of metasurfaces with other holographic functionalities.
Keywords: tet_topic_meta

Gnaden-Gegenwart - Bach als Praktischer Theologe. Zum Amtsantritt des Thomaskantors vor 300 Jahren. Klaus Hock / Thomas Klie (Hg.): Bachzitate, Bielefeld 2021 - Ingo Bredenbach / Volker Leppin / Christoph Schwöbel (Hg.): Bach unter Theologen, Tübingen 2022 - Schroeter-Wittke, Harald (Praktische Theologie)

Outcomes-based contracting and public management reform: Lessons from a decade of experimentation - FitzGerald, Clare; Fraser, Alec; Kimmitt, Jonathan; Knoll, Lisa; Williams, James (International Public Management Journal)
Keywords: Public Administration; Business and International Management

Theoretical analysis of four-wave mixing on semiconductor quantum dot ensembles with quantum light - Rose, Hendrik; Grisard, S.; Trifonov, A. V.; Reichhardt, R.; Reichelt, Matthias; Bayer, M.; Akimov, I. A.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of an ensemble of semiconductor quantum dots is analyzed by wave-mixing processes, where we focus on four-wave mixing with two incident pulses. Wave-mixing experiments are often described with semiclassical models, where the light is modeled classically and the material quantum mechanically. Here, however, we use a fully quantized model, where the light is given by a quantum state of light. Quantum light involves more degrees of freedom than classical light as e.g., its photon statistics and quantum correlations, which is a promising resource for quantum devices, such as quantum memories. The light-matter interaction is treated with a Jaynes-Cummings type model and the quantum field is given by a single mode since the quantum dots are embedded in a microcavity. We present numerical simulations of the four-wave-mixing response of a homogeneous system for pulse sequences and find a significant dependence of the result on the photon statistics of the incident pulses. The model constitutes a problem with a large state space which arises from the frequency distribution of the transition energies of the inhomogeneously broadened quantum dot ensemble that is coupled with a quantum light mode. Here we approximate the dynamics by summing over individual quantum dot-microcavity systems. Photon echoes arising from the excitation with different quantum states of light are simulated and compared.

Alternative für alle? Inklusionsspezifische Analyse der AfD und ihrer Wähler*innen - Freymuth, Nina (Diskriminierungsprozesse und Teilhabeperspektiven - Herausforderungen für die Praxis der Inklusion. Ausgewählte Master-Thesen 2018-2022 des Masterstudiengangs "Soziale Inklusion: Gesundheit und Bildung" der Evangelischen Hochschule Rheinland-Westfalen-Lippe)

Approximate Computing: Balancing Performance, Power, Reliability, and Safety - Badran, Abdalrhman; Sadeghi-Kohan, Somayeh; Reimer, Jan Dennis; Hellebrand, Sybille (28th IEEE European Test Symposium (ETS'23), May 2023)

Integrating driver behavior into last-mile delivery routing: Combining machine learning and optimization in a hybrid decision support framework - Dieter, Peter; Caron, Matthew; Schryen, Guido (European Journal of Operational Research (EJOR))

Are Women (Really) More Lenient? Gender Differences in Expert Evaluations - Frick, Bernd; Spiess Bru, Clarissa; Kaimann, Daniel

Sounds too Feminine? Brand Gender and The Impact on Professional Critics - Kaimann, Daniel; Spiess Bru, Clarissa

Essays on Choices and Behavior in Competitive Situations - Beck-Werz, Lisa

Von der Grundschule in die Sekundarstufe. Übergänge ressourcenorientiert gestalten (Hrsg. von Petra Büker) - Herding, Jana; Carle, U.

‘I Feel Well, Accepted and Competent in School’—Determinants of Self-Perceived Inclusion and Academic Self-Concept in Students with Diagnosed Behavioral, Emotional and Social Difficulties (BESD) - Zdoupas, Philippos; Laubenstein, Désirée (Social Sciences)

Approximation Algorithms for Fair Range Clustering - Hotegni, Sedjro Salomon; Mahabadi, Sepideh; Vakilian, Ali (Proceedings of the 40th International Conference on Machine Learning, Honolulu, Hawaii, USA. PMLR 202, 2023.)
Keywords: Fair range clustering

The Hermeneutics of al-Sharīf al-Murtaḍā (d. 436/1044) in the Interpretation of Akhbār al-Āḥād in his Kitāb al-Amālī - Aghaei Abrandabadi, Seyed Ali (Hadith Commentary: Continuity and Change)

We Really Need to Talk About Session Tickets: A Large-Scale Analysis of Cryptographic Dangers with TLS Session Tickets - Hebrok, Sven Niclas; Nachtigall, Simon; Maehren, Marcel; Erinola, Nurullah; Merget, Robert; Somorovsky, Juraj; Schwenk, Jörg (32nd USENIX Security Symposium)

Weisheit und moralischer Intellektualismus im Koran aus intertextueller Perspektive - Dorogova, Elizaveta (Hermeneutiken der Weisheit)

Overcoming Diffusion Limitation of Faradaic Processes: Property‐Performance Relationships of 2D Conductive Metal‐Organic Framework Cu3(HHTP)2 for Reversible Lithium‐Ion Storage - Wrogemann, Jens Matthies; Lüther, Marco Joes; Bärmann, Peer; Lounasvuori, Mailis; Javed, Ali; Tiemann, Michael; Golnak, Ronny; Xiao, Jie; Petit, Tristan; Placke, Tobias; Winter, Martin (Angewandte Chemie International Edition)
Faradaic reactions including charge transfer are often accompanied with diffusion limitation inside the bulk. Conductive two-dimensional frameworks (2D MOFs) with a fast ion transport can combine both - charge transfer and fast diffusion inside their porous structure. To study remaining diffusion limitations caused by particle morphology, different synthesis routes of Cu-2,3,6,7,10,11-hexahydroxytriphenylene (Cu3(HHTP)2), a copper-based 2D MOF, are used to obtain flake- and rod-like MOF particles. Both morphologies are systematically characterized and evaluated for redox-active Li+ ion storage. The redox mechanism is investigated by means of X-ray absorption spectroscopy, FTIR spectroscopy and in situ XRD. Both types are compared regarding kinetic properties for Li+ ion storage via cyclic voltammetry and impedance spectroscopy. A significant influence of particle morphology for 2D MOFs on kinetic aspects of electrochemical Li+ ion storage can be observed. This study opens the path for optimization of redox active porous structures to overcome diffusion limitations of Faradaic processes.
Keywords: General Chemistry; Catalysis

Control of the electron dynamics in solid-state high harmonic generation on ultrafast time scales by a polarization-skewed laser pulse - Song, Xiaohong; Yang, Shidong; Wang, Guifang; Lin, Jianpeng; Wang, Liang; Meier, Torsten; Yang, Weifeng (Optics Express)
Since high-order harmonic generation (HHG) from atoms depends sensitively on the polarization of the driving laser field, the polarization gating (PG) technique was developed and applied successfully to generate isolated attosecond pulses from atomic gases. The situation is, however, different in solid-state systems as it has been demonstrated that due to collisions with neighboring atomic cores of the crystal lattice strong HHG can be generated even by elliptically- and circularly-polarized laser fields. Here we apply PG to solid-state systems and find that the conventional PG technique is inefficient for the generation of isolated ultrashort harmonic pulse bursts. In contrast, we demonstrate that a polarization-skewed laser pulse is able to confine the harmonic emission to a time window of less than one-tenth of the laser cycle. This method provides a novel way to control HHG and to generate isolated attosecond pulses in solids.
Keywords: Atomic and Molecular Physics; and Optics